2015
DOI: 10.1371/journal.ppat.1005254
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-α Subtypes in an Ex Vivo Model of Acute HIV-1 Infection: Expression, Potency and Effector Mechanisms

Abstract: HIV-1 is transmitted primarily across mucosal surfaces and rapidly spreads within the intestinal mucosa during acute infection. The type I interferons (IFNs) likely serve as a first line of defense, but the relative expression and antiviral properties of the 12 IFNα subtypes against HIV-1 infection of mucosal tissues remain unknown. Here, we evaluated the expression of all IFNα subtypes in HIV-1-exposed plasmacytoid dendritic cells by next-generation sequencing. We then determined the relative antiviral potenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
161
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 89 publications
(181 citation statements)
references
References 78 publications
16
161
2
Order By: Relevance
“…Human gut LPMCs from 6 different donors (each in duplicate) were obtained following tissue disaggregation and collagenase digestion (43,44). The LPMCs were spinoculated with HIV-1 BaL at 10 ng p24/10 6 cells (AIDS Research Reagent Program; catalog number 4984) and resuspended in different IFN-␣2 or IFN-␣14 concentrations, and the percentage of p24 ϩ cells in the CD3 ϩ CD8 Ϫ cell fraction was evaluated at 4 days postinfection (dpi) by flow cytometry, as previously described (14). The recombinant IFN-␣2 and IFN-␣14 proteins were purchased from PBL Assay Science (catalog number 11002-1).…”
Section: Ethicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Human gut LPMCs from 6 different donors (each in duplicate) were obtained following tissue disaggregation and collagenase digestion (43,44). The LPMCs were spinoculated with HIV-1 BaL at 10 ng p24/10 6 cells (AIDS Research Reagent Program; catalog number 4984) and resuspended in different IFN-␣2 or IFN-␣14 concentrations, and the percentage of p24 ϩ cells in the CD3 ϩ CD8 Ϫ cell fraction was evaluated at 4 days postinfection (dpi) by flow cytometry, as previously described (14). The recombinant IFN-␣2 and IFN-␣14 proteins were purchased from PBL Assay Science (catalog number 11002-1).…”
Section: Ethicsmentioning
confidence: 99%
“…A recent in vitro study using human gut LPMCs showed that the antiviral effects of different IFN-␣ subtypes on HIV-1 suppression were not equal (14). To assess and confirm the best IFN-␣ subtypes to follow up with experiments in humanized mice, we conducted an in vitro screening assay.…”
Section: Antiviral Activities Of Ifn-␣ Subtypes On Hiv-1 Replicationmentioning
confidence: 99%
See 3 more Smart Citations